AN INQUIRY INTO SHAKESPEARE’S "A MIDSUMMER NIGHT’S DREAM": USING THE LENS OF MORPHOLOGICAL AMBIGUITY BY RAY JACKENDOFF - Mrs Nadia Sheheryar; Sumayya Mubarak (International Journal of Contemporary Issues in Social Sciences, 2024)
Shakespeare’s "A Midsummer Night’s Dream" is a literary classic that is appreciated worldwide for its complex language and multiple meanings. This research paper will explore the play through morphological ambiguity, which is the theory of Ray Jackendoff. The morphological ambiguity, which is the process of a word or phrase having different meanings based on its form, is the phenomenon that will reveal new levels of interpretation in Shakespeare’s works. Through the use of linguistic analysis tools and methodologies, this research aims to get to the roots of the subtle nuances and the several layers of meaning that are hidden in the text. The paper deals with a detailed analysis of some main passages, and as a result, it will help to acquire a deeper understanding of Shakespearean linguistics and literary interpretation. In the end, this research may be of great significance for the study of literature and language as it shows the intimate relationship between linguistic structures and literary meaning.